Scanning X‐ray diffraction on cardiac tissue: automatized data analysis and processing. (23rd October 2017) - Nicolas, Jan-David; Bernhardt, Marten; Markus, Andrea; Alves, Frauke; Burghammer, Manfred; Salditt, Tim
Abstract : An entire tissue slice of a mouse heart has been analyzed by scanning X‐ray diffraction, using a micrometer spot sized beam and analyzed using an analysis toolbox that is provided for general use. In this way, variations of the local molecular structure parameters of the sarcomere, the basic structural unit of the myofibrils which make up muscle fibers, can be assessed, such as local orientation, strain and variation in filament lattice spacing. Abstract : A scanning X‐ray diffraction study of cardiac tissue has been performed, covering the entire cross section of a mouse heart slice. To this end, moderate focusing by compound refractive lenses to micrometer spot size, continuous scanning, data acquisition by a fast single‐photon‐counting pixel detector, and fully automated analysis scripts have been combined. It was shown that a surprising amount of structural data can be harvested from such a scan, evaluating the local scattering intensity, interfilament spacing of the muscle tissue, the filament orientation, and the degree of anisotropy. The workflow of data analysis is described and a data analysis toolbox with example data for general use is provided. Since many cardiomyopathies rely on the structural integrity of the sarcomere, the contractile unit of cardiac muscle cells, the present study can be easily extended to characterize tissue from a diseased heart.